Des usages néolibéraux de Spinoza : les cas du développement personnel et de la philosophie du management - Vincent Mariscal (Astérion)
This article is about specific uses of the thought of Spinoza, studied through a selection of books concerning personal development and philosophy of management. Through a discourse of truth and authority, these texts give rise to the formulation of a Spinozism that philosophically justifies the ideal types of neoliberalism and make Spinoza the father of this social, political, and economic model. Thus, the authors want to convince individuals that they must concentrate on their affects, by postulating that happiness and freedom can only be achieved by working on oneself. However, this means minimising the influence of a social exteriority that remains crucial to Spinozian philosophy. This article studies what has been retained from the Spinozian corpus, to make it correspond to neoliberalism and to apply these practices of personal development and philosophy of management. We also point out the limits of this singular interpretation of Spinoza, while questioning the relevance of this type of adaptation of his philosophy to contemporary times.